An Eco-Sustainable Stabilization of Clayey Road Subgrades by Lignin Treatment: An Overview and a Comparative Experimental Investigation - Rosolino Vaiana; Cesare Oliviero Rossi; Giusi Perri (Applied Sciences, 2021)
Subgrade conditions significantly affect functionality of the road pavement during its service life. Among the different stabilization techniques for upgrading poorly performing in-situ soil subgrades, an economically attractive example involves the use of waste materials, such as lignin. A deep bibliographic analysis of previous studies is carried out in the first section of this paper. The literature review suggests that use of lignin as a stabilizing agent of road subgrade soils is not completely consolidated. In addition, this study reports an investigation on the strength and performance characteristics of a lignin-treated clayey soil. Several experimental tests were carried out on both the untreated and lignin-treated soils in order to shed some light on different aspects with limited knowledge available, such as the behaviour of the stabilised soil in specific conditions (e.g., the presence of water). Finally, the test results are discussed and compared with those obtained when the same soil is treated with lime, which is more widely used. The most relevant finding is the poor ability of lignin to upgrade the bearing capacity of the soil in wet conditions compared to lime; on the contrary, the presence of lignin helped in controlling the swelling potential of this type of soil.